2015
DOI: 10.1038/nnano.2015.192
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Hall resistance standard in graphene devices under relaxed experimental conditions

Abstract: The quantum Hall effect provides a universal standard for electrical resistance that is theoretically based on only the Planck constant h and the electron charge e. Currently, this standard is implemented in GaAs/AlGaAs, but graphene's electronic properties have given hope for a more practical device. Here, we demonstrate that the experimental conditions necessary for the operation of devices made of high-quality graphene grown by chemical vapour deposition on silicon carbide can be extended and significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
129
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(142 citation statements)
references
References 42 publications
7
129
1
1
Order By: Relevance
“…To the data in Figure 2 we fitted a power law of the form + ( /nA) which had successfully been used in extrapolating the Hall resistance of a GaAs-based QHE device in the fractional QH state at filling factor 1/3 recently [19] and which also has been observed for an integer QHE device [23]. Interestingly, in all cases an exponent of 3 is observed in this power law, for the cited IQHE and FQHE measurements as well as for the QAHE result obtained here.…”
Section: In This Tablementioning
confidence: 99%
“…To the data in Figure 2 we fitted a power law of the form + ( /nA) which had successfully been used in extrapolating the Hall resistance of a GaAs-based QHE device in the fractional QH state at filling factor 1/3 recently [19] and which also has been observed for an integer QHE device [23]. Interestingly, in all cases an exponent of 3 is observed in this power law, for the cited IQHE and FQHE measurements as well as for the QAHE result obtained here.…”
Section: In This Tablementioning
confidence: 99%
“…The quantum plateaus in G/SiC devices are much larger in magnetic field than those obtained in graphene encapsulated in hBN [7], because they are stabilized by charge transfer [8] and disorder [9]. Thanks to these properties, it was recently demonstrated that G/SiC can act as a quantum electrical resistance standard [10], even in experimental conditions relaxed with respect to the state of the art in GaAs-based quantum wells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Low-frequency noise, also referred to as flicker noise or 1/f noise, is a common phenomenon caused by various physical mechanisms and found in numerous systems [4,5], including electronic transport in graphene devices [6][7][8][9]. At low temperature, the noise properties of graphene are of particular interest for its application in metrology as a quantum Hall resistance [10][11][12][13] and impedance [14] standard. In low-temperature diffusive transport in a disordered conductor like graphene, quantum interference effects arise due to the phase-coherent transport of electrons.…”
Section: Introductionmentioning
confidence: 99%